2005
DOI: 10.1021/jm050467q
|View full text |Cite
|
Sign up to set email alerts
|

Novel 4-Oxo-1,4-dihydroquinoline-3-carboxamide Derivatives as New CB2 Cannabinoid Receptors Agonists:  Synthesis, Pharmacological Properties and Molecular Modeling

Abstract: Recent data indicated that the CB(2) cannabinoid receptor constitutes an attractive drug target due to its potential functional role in several physiological and pathological processes. A set of 4-oxo-1,4-dihydroquinoline-3-carboxamide derivatives, characterized by the presence of some important structural requirements exhibited by other classes of cannabinoid ligands, such as an aliphatic or aromatic carboxamide group in position 3, and an alkyl or benzyl group in position 1, was synthesized and assayed to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
107
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 57 publications
(122 reference statements)
10
107
0
Order By: Relevance
“…The cyclization of the enamines 16 is realized by the action of heat in high-boiling solvents such as biphenyl [44], biphenyl ether [1, 26,32,34,36,37,41,42,[45][46][47], Dowtherm A [35,38,39,48,49], and mineral oil [1] or by using effective cyclization agents such as polyphosphoric acid or its esters [1, 2], the halogen derivatives of phosphorus [1], ZnCl 2 [1], conc. sulfuric acid in mixture with acetic anhydride [1], and Eaton's reagent (a mixture of phosphorus(V) oxide and methanesulfonic acid) [37,40].…”
Section: Type Dmentioning
confidence: 99%
“…The cyclization of the enamines 16 is realized by the action of heat in high-boiling solvents such as biphenyl [44], biphenyl ether [1, 26,32,34,36,37,41,42,[45][46][47], Dowtherm A [35,38,39,48,49], and mineral oil [1] or by using effective cyclization agents such as polyphosphoric acid or its esters [1, 2], the halogen derivatives of phosphorus [1], ZnCl 2 [1], conc. sulfuric acid in mixture with acetic anhydride [1], and Eaton's reagent (a mixture of phosphorus(V) oxide and methanesulfonic acid) [37,40].…”
Section: Type Dmentioning
confidence: 99%
“…Earlier syntheses [4] of N-substituted 1,4-dihydro-4-oxo-3-quinolinecarboxylate esters have generally followed two strategies. In the first, conjugate addition of aniline to diethyl (ethoxymethylene)malonate to give a b-enamino diester was followed by thermal ring closure at 250 C and N-alkylation (overall yield ca.…”
Section: Introductionmentioning
confidence: 99%
“…50%). The disadvantage of this method is the high temperature used for the cyclization reaction, and the highly variable yields in the final alkylation [4,5]. For N-aryl cases, where alkylation by an S N 2 reaction is not possible, diphenylamine (the only case reported) was used to prepare the initial b-enamino diester [6].…”
Section: Introductionmentioning
confidence: 99%
“…Functionality studies revealed the CB 2 cannabinoid receptor agonistic properties of our derivatives. 16,17 A lot of studies have shown that enantiomers of many drugs, including cannabinoid ligands, present different pharmacological profiles, independent metabolic pathways or various levels of toxicity. 18 Compounds 1-8 are characterized by a chiral center as shown in Figure 1.…”
mentioning
confidence: 99%
“…The distomer (1)-1 exhibited an affinity of 784 nM which highlighted the stereoselective interaction to the CB 2 receptor. 16 Previous studies using liquid chromatography for the analytical resolution of 4-quinolone derivatives used derivatization procedures, or chiral mobile phase methods based on ligand exchange, or chiral stationary phases (CSPs) methods including crown ether, protein-based CSPs. 19 Further cellulose and amylose ester and carbamate derivatives coated onto a largepore silica gel backbone have proved to be extremely useful CSPs for chiral resolution and to the best of our knowledge, only a study by Radhakrishna et al 20 described the resolution of fluoroquinolone Moxifloxacin enantiomers on a cellulose carbamate derivative (Chiralcel OD-H) and on cellulose ester derivatives (Chiralcel OJ and OB).…”
mentioning
confidence: 99%